A Comparative Study on the Mastery and Implementation of TPACK among Teachers in the Philippines and Indonesia: An Analysis of Contextual Factors and Their Impact on Teaching - Khairunnisak, Rania (International Conference on Elementary Education, 2025)
This study examines the differences in mastery and implementation of TPACK among teachers in Indonesia and the Philippines through a comparative and contextual analysis approach. Quantitative data reveal higher TPACK mastery levels among Filipino teachers, supported by policies, ongoing professional development, and adequate infrastructure, while Indonesian teachers face resource and sustainability constraints. Qualitative analysis uncovers the influence of cultural, policy, and resource factors on pedagogical practices and development models. Findings highlight that successful TPACK implementation is heavily dependent on systemic and environmental factors, emphasizing the need for adaptive, context-based policy strategies. These insights serve as a vital reference for designing innovative, sustainable, and relevant technology-integration policies within ASEAN educational frameworks.